Analysis of Flexural Bearing Capacity and Failure Mode of Precast LSFRC Pavement Slab - Zi-Jian Wang; Yi-Xuan Ban; Wen-Yu Luo; Han-Xiu Fan; Bin Zhang; Li-Ming Wu; Si-Chang Wang (Advances in Materials Science and Engineering)
To promote practical use of the top-and-bottom layered steel fiber reinforced concrete (LSFRC) plates, an appropriate constitutive model is selected using ABAQUS software to analyze the bearing capacity, failure pattern, and deformation of the LSFRC plates. An LSFRC plate model is established for the analysis and calculation. Meanwhile, a test was carried out to measure the bearing capacity of 10 LSFRC plates. The results show that, after going through the elastic stage, crack growth, and failure stage, when the maximum crack width reaches 0.1 mm, the load of the LSFRC plates can be used as the ultimate bearing load. When failure appears to be bending the LSFRC plates, the neutral axis will shift upwards, showing a pseudoplastic failure. There is a larger tensile stress area after the first crack appears at the bottom of the steel fiber concrete. The change before and after the maximum load is relatively gentle. After becoming plastic, the plate witnesses a rapid crack growth on its bottom. With similar results from the test and numerical simulation, small errors can be minimized by further analysis to provide a more accurate model for the subsequent bearing capacity analysis of the LSFRC plates.